Continuous visual stimulus tracking to quantify eye motility in spinocerebellar ataxia type 3 - de Boer, M. J.; Wasmann, R. A.; Pott, J. W. R.; Cornelissen, F. W.; Jansonius, N. M. (Frontiers in Neurology, 2025)
IntroductionSpinocerebellar ataxias (SCA) form a group of dominantly inherited neurodegenerative diseases represented by progressive cerebellar ataxia and various other neurological deficits. SCA3 is the most prevalent type globally and represents 28% of the autosomal dominant cerebellar ataxias in The Netherlands. The associated oculomotor disorders, with distance esotropia as its hallmark, cause diplopia and often present early. To gain further insight into this, we examined eye movements made during a continuous visual stimulus tracking task (SONDA; Standardized Oculomotor and Neuro-Ophthalmic Disorder Assessment).MethodsThirteen genetically confirmed SCA3 cases underwent SONDA, both monocularly and binocularly. As a reference, we used previously collected data from 36 monocularly and 13 binocularly measured healthy subjects.ResultsSCA3 cases were well capable of tracking the moving stimulus, but they performed the task differently. More specifically, their eyes were not synchronized in their movements, and they made multiple small saccades in response to a large stimulus jump instead of a larger saccade followed by a small corrective saccade. The saccadic amplitude distribution shape was related to the severity of the oculomotor disorder, suggesting that the saccadic amplitude distribution could be used as a biomarker of disease severity.ConclusionOverall, this study highlights that eye-tracking during a standardized task can give valuable insights into how eye movements are affected in SCA3 and provides suggestions for potential biomarkers for severity and the associated treatment options. Longitudinal research is needed to elaborate on these findings and validate the proposed biomarkers.